Mammographic findings of Breast Cancer: review of 43 cases in IIUM Breast Centre (2008-2010) - Hassan, Radhiana; Che Mohamed, Siti Kamariah; Abdul Rashid, Mohd Amran; Yahaya, Azura Sharena; Muhammed Nordin, Ellyda; Zaini, Izwan Zanni (2011)
INTRODUCTION Breast cancer is the most common malignant disease among Malaysian women. During a 3-year period from 2003 until 2005, 11952 new cases of breast cancer were reported to the National Cancer Registry. Mammography plays an important role in the diagnostic assessment and screening of breast cancer.